1996
DOI: 10.1212/wnl.46.5.1359
|View full text |Cite
|
Sign up to set email alerts
|

Central motor loop oscillations in parkinsonian resting tremor revealed magnetoencephalography

Abstract: A variety of clinical and experimental findings suggest that parkinsonian resting tremor results from the involuntary activation of a central mechanism normally used for the production of rapid voluntary alternating movements. However, such central motor loop oscillations have never been directly demonstrated in parkinsonian patients. Using magnetoencephalography, we recorded synchronized and tremor-related neuromagnetic activity over wide areas of the frontal and parietal cortex. The spatial and temporal orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
169
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(188 citation statements)
references
References 17 publications
17
169
2
Order By: Relevance
“…The pathophysiological effects of PD on the thalamus thus lead to a slowing of scalp EEG in PD patients (Soikkeli et al, 1991;Stanzione et al, 1996;Tanaka et al, 2000). Our results support the notion that the PD symptomatology originates from a disturbance in the thalamocortical interplay (Llinas, 1984;Volkmann et al, 1992Volkmann et al, , 1996Llinas and Pare, 1994;Jeanmonod et al, 1996;Llinas et al, 1999).…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…The pathophysiological effects of PD on the thalamus thus lead to a slowing of scalp EEG in PD patients (Soikkeli et al, 1991;Stanzione et al, 1996;Tanaka et al, 2000). Our results support the notion that the PD symptomatology originates from a disturbance in the thalamocortical interplay (Llinas, 1984;Volkmann et al, 1992Volkmann et al, , 1996Llinas and Pare, 1994;Jeanmonod et al, 1996;Llinas et al, 1999).…”
Section: Introductionsupporting
confidence: 81%
“…(5) In the final step, positive symptoms are produced (e.g., tremor) (Volkmann et al, 1992(Volkmann et al, , 1996. This step is thought to be related to the reciprocal corticocortical inhibition mediated by GABAergic interneurons, which is a general feature of cortical organization (Fig.…”
Section: Mechanism Of Pd Symptomsmentioning
confidence: 99%
“…The main output of the basal ganglia is indeed via the pallidothalamic tract into the thalamus. Due to a reduction of dopamine in the striatum, increased neuronal activity of the internal part of the globus pallidus (GPi) (Albin et al, 1989;Beric et al, 1996;DeLong, 1990;Hutchison et al, 1994;Lozano et al, 1998;Magnin et al, 2000;Sterio et al, 1994), causes a tonic overinhibition of the pallidal-recipient thalamic relay cells leading to a thalamocortical dysrhythmic interplay, named thalamocortical dysrhythmia (TCD), characterized by an overproduction of thalamic low threshold calcium spike bursts and an increase in low and high frequency EEG power (Jeanmonod et al, 1996Llinas, 1984;Llinas and Pare, 1994;Llinás et al, 2001;Llinás et al, 1999;Magnin et al, 2000;Volkmann et al, 1992Volkmann et al, , 1996.…”
Section: Introductionmentioning
confidence: 99%
“…Network locations have been examined by EEG and MEG in patients with PD, however, the tremor origin has not been accurately located. It has been shown by MEG that a tremor correlates with cortical activities 14 . Hellwig et al 9 also showed tremor-correlated cortical activities in EEG recordings indicating significant coherency to the unilateral tremor in the contralateral motor cortex area.…”
Section: Discussionmentioning
confidence: 99%